Determinação das propriedades mecânicas em tração de compósitos de matriz poliéster reforçados com fibras longas de guarumã (Ischnosiphon arouma) - LIMA, Rodolfo Moura de Souza (2022)
Environmental concerns have become increasingly frequent, driving the development of alternative materials using renewable resources. In this sense, the polymer matrix composite materials with the use of vegetable fibers as reinforcement stand out. Vegetable fibers stand out for their abundance in nature, low cost, in addition to presenting satisfactory results when compared to synthetic fibers. In this context, it is possible to highlight the Guarumã (Ischnosiphon arouma) an abundant species from the Amazon region and widely used in the making of basketry crafts. Thus, this work aims to produce polyester matrix composites, using Guarumã fibers as reinforcement. The process of making the composites began with the analyze of the fibers, the specimens were produced individually in a silicone mold with the incorporation of 10, 20 and 30% by volume of fibers. The tensile mechanical properties of the composites were evaluated according to the guidelines of the ASTM D 638 standard. The results obtained revealed that the incorporation of Guarumã fibers in polyester matrix did not significantly alter the values obtained in relation to pure resin, however, the Guarumã fiber reveals great potential as a reinforcement in composite materials.